Pengaruh Penggunaan Aplikasi â€œSi Pesekâ€ (Stop Tindakan Pelecehan Seksual) Terhadap Pengetahuan Tentang Personal Safety Skill Pada Anak Usia Prasekolah di TK Manbaâ€™ul Huda Bekasi - Beri, Edo Septa; Sutini, Titin; haryanto, Rohadi (Universitas Mohammad Husni Thamrin, 2021)
Sexual child abuse is involving, persuading, or forcing a child to take part in sexual activities or encouraging Â the child to behave inappropriate sexual contact, and this is a frequent phenomenon. The purpose of this study was to identify the effect of using the application â€œsi pesekâ€ on personal safety skill knowledge in preschool children at Manbaâ€™ul Huda, Bekasi, West Java. The research design used was the equations experimental non equivalent control grop design with 30 respondents divided into two groups, intervention dan control. The result showed that the ads were the effect of giving the application â€œsi pesekâ€ on personal knowledge of safety skill with a p value 0.000 (<0.05). There is an effect of confounding factors on children knowledge, namely age with p value 0.04 (<0.05), environment with p value 0.04 (<0.05), socio cultural with p value 0.04 (<0.05) and information is the most significant with p value 0.02 (<0.05). Based on the research results the application â€œsi pesekâ€ can be recommended as an educational tool in child nursing services to prevent sexual violence in preschoolersKeywords: Preschool children, sexual education, sexual abuseÂ